Yield and the 15N Fate in Rice/Maize Season in the Yangtze River Basin. (1st March 2019) - Wang, Sen; Yang, Min; Liao, Shipeng; Sheng, Weihong; Shi, Xiaojun; Lu, Jianwei; Guo, Shiwei; Shen, Jianbo; Zhang, Fusuo; Goulding, Keith; Liu, Xuejun
Abstract : Core Ideas: Yield and 15 N fate were studied in rice/maize season in Yangtze River Basin. Rice/maize yields were comparable between traditional and reduced fertilizer rate. Reduced fertilizer increased N use efficiency and reduced N loss to environment. Reduced fertilizer showed 40% N and 50% P saving potential in the rice/maize season. The deterioration of water quality induced by overuse of N and P fertilizers has become one of the main limiting factors of the sustainable economic and social development of the Yangtze River Basin (YRB), China. Three field experiments using 15 N‐labeled urea were conducted at three locations in upstream, midstream, and downstream regions of YRB to evaluate the impacts of improved fertilizer management (reduced rates and better timing of the applications compared to a traditional, high N application) on crop yield, fertilizer N recovery, and fate in a rice ( Oryza sativa L.)‐flooded fallow rotation (RF), a rice–wheat ( Triticum aestivum L.) rotation (RW), a rice‐flooded fallow rotation (RF), a rice–vegetable rotation (RV), and a maize ( Zea mays L.) –wheat rotation (MW). The improved fertilizer treatment significantly increased rice grain yield by 12.9% compared with the high fertilizer treatment in a RW rotation in Rugao (Jiangsu), but had no significant effect on rice grain yield in the other rotations. It led to significantly lower maize yields in Jiangjin (Chongqing). The total fertilizer N recoveries in rice and in the 0 to 40 cm soil were 17 to 35% and 17 to 32%, with crop and/or soil recoveries usually higher in the improved fertilizer treatments than in the traditional fertilizer treatments, but not for maize. Fertilizer N losses can be reduced by using improved fertilizer management in a rice‐based rotation. An improved fertilizer management which has 60% N and 50% P application of the traditional fertilizer application can produce a sustained high rice yield and reduce the environmental impact compared with traditional fertilizer input used in the YRB.